Manutenção e retirada dos contratos administrativos inválidos - Freire, André Luiz (2007)
The main purpose of this work is to argue about the ways to continue or terminate with the agreements executed by the Estate (or its companies) that were declared invalid ( Administrative Contracts ). Starting from the premise that Administrative Contracts, as any other legal actions, insert normative rulings on the statutory law system, it is necessary to know whenever they will be considerer valid or not valid. Therefore, it shall be important, under this work, to clarify the sense of the word effectiveness . Afterwards, it will be stated the concept of Administrative Contract that is adopted herein, which is based on the principles and prerequisites of the public actions. This shall be useful for the discussion of the revalidation of the invalid Administrative Contract. Once we present, according to the Brazilian law, the concept of the invalidity and its varieties, it will broach the hypotheses for the maintenance of an invalid Administrative Contract on the statutory law, which are the revalidation, the conversion and the remedy. At last, the invalidation and the suspension of the enforcement of an invalid Administrative Contract by the Legislative Branch and by the Public Finance Court which both are means to cancel invalid Administrative Contracts shall be object of our analysis